A novel NIR long phosphorescent phosphor:SrSnO3:Bi2+. Issue 123 (24th November 2015) - Qin, Xixi; Li, Yang; Wu, Dakun; Wu, Yiling; Chen, Ruchun; Ma, Zhijun; Liu, Shijian; Qiu, Jianrong
Abstract : A novel phosphor with near-infrared (NIR) long persistent luminescence, SrSnO3 :Bi 2+ was successfully synthesized by traditional solid-state reaction. Abstract : A novel phosphor with near-infrared (NIR) long persistent luminescence, SrSnO3 :Bi 2+ was successfully synthesized by traditional solid-state reaction. The phosphor shows deep red-NIR persistent luminescence with a broad emission band from 700 to 900 nm peaking at 808 nm, as well as a persistence time of >30 min. This phosphor has broken the domination of conventional Cr 3+, Mn 2+ and Mn 4+ -activated long persistent phosphors and provides a new perspective on the NIR phosphorescence of Bi-doped long phosphorescent phosphors. Meanwhile, the characteristic operational waveband offer the possibility of potentially being applied in vivo bio-imaging of this new NIR phosphorescent material.